Monitoring of Antimicrobial Susceptibility of Bacteria Isolated from Poultry Farms from 2014 to 2018 - Engy Ahmed Hamed; May Fathy Abdelaty; Hend Karam Sorour; Heba Roshdy; Mona Aly Abdelhalim AbdelRahman; Ola Magdy; Waleed Abdelfatah. Ibrahim; Ahmed Sayed; Hytham Mohamed; Mohammed Iraqi Youssef; Wafaa Mohamed Hassan; Heba Badr (Veterinary Medicine International)
The current situation of antibiotic resistance of most bacterial pathogens was a threat to the poultry and public health with increasing economic losses. Regarding this problem, monitoring of the circulating microorganisms occurred with the antibiotic resistance profile. A total of 657 different samples from internal organs (liver, heart, lung, and yolk) and paper-lining chick boxes were collected from native chicken farms which were submitted to the Reference Laboratory for Veterinary Quality Control on Poultry Production in the period from 2014 to 2018 for the detection of Salmonella, Escherichia coli (E. coli), and Staphylococcus. The bacterial isolates were tested for their antimicrobial susceptibility by disk diffusion technique. Salmonella was isolated from 128 out of 657 (19.5%), E. coli was isolated from 496 out of 657 (75.5%), and Staphylococcus species was isolated from 497 out of 657 (75.6%). All Salmonella positive samples were examined for antibiotic resistance against 10 different antibiotics, and the highest percentage all over the five years was against penicillin, ampicillin, and tetracycline. All E. coli positive samples were examined for antibiotic resistance against 14 different antibiotics, and the highest percentage all over the five years was with ampicillin, tetracycline, norfloxacin, streptomycin, and danofloxacin. All Staphylococcus positive sample species were examined for antibiotic resistance against 14 different antibiotics, and the highest percentage of resistance all over the five years was shown with tetracycline, streptomycin, ampicillin, and nalidixic acid.